Dentine oxygen isotopes (δ18O) as a proxy for odontocete distributions and movements. Issue 14 (8th June 2016) - Matthews, Cory J. D.; Longstaffe, Fred J.; Ferguson, Steven H.
Abstract: Spatial variation in marine oxygen isotope ratios ( δ 18 O) resulting from differential evaporation rates and precipitation inputs is potentially useful for characterizing marine mammal distributions and tracking movements across δ 18 O gradients. Dentine hydroxyapatite contains carbonate and phosphate that precipitate in oxygen isotopic equilibrium with body water, which in odontocetes closely tracks the isotopic composition of ambient water. To test whether dentine oxygen isotope composition reliably records that of ambient water and can therefore serve as a proxy for odontocete distribution and movement patterns, we measured δ 18 O values of dentine structural carbonate ( δ 18 OSC ) and phosphate ( δ 18 OP ) of seven odontocete species ( n  = 55 individuals) from regional marine water bodies spanning a surface water δ 18 O range of several per mil. Mean dentine δ 18 OSC (range +21.2 to +25.5‰ VSMOW) and δ 18 OP (+16.7 to +20.3‰) values were strongly correlated with marine surface water δ 18 O values, with lower dentine δ 18 OSC and δ 18 OP values in high‐latitude regions (Arctic and Eastern North Pacific) and higher values in the Gulf of California, Gulf of Mexico, and Mediterranean Sea. Correlations between dentine δ 18 OSC and δ 18 OP values with marine surface water δ 18 O values indicate that sequential δ 18 O measurements along dentine, which grows incrementally and archives intra‐ and interannual isotopic composition over the lifetime of the animal, would be useful for characterizing residency within and movements among water bodies with strong δ 18 O gradients, particularly between polar and lower latitudes, or between oceans and marginal basins. Abstract : Spatial variation in marine oxygen isotope ratios ( δ 18 O) is potentially useful for characterizing marine mammal distributions and tracking movements across δ 18 O gradients. We measured δ 18 O values of dentine structural carbonate ( δ 18 OSC ) and phosphate ( δ 18 OP ) of odontocetes from regional marine water bodies spanning a range of surface water δ 18 O values and found strong correlations between dentine and marine surface water δ 18 O values. Results indicate sequential δ 18 O measurements along dentine, which grows incrementally and archives intra‐ and interannual isotopic composition over the lifetime of the animal, would be useful for characterizing residency within and movements among water bodies with strong δ 18 O gradients, particularly between polar and lower latitudes, or between oceans and marginal basins.